Pension Privileges the Economic and Social Aspects - Walczak, Damian (Studia Oeconomica Posnaniensia, 2017)
In Poland there are a number of pension privileges. Every privilege ultimately results in developing different rules for calculating insurance contributions (e.g. farmers), payment of benefits (based on the principle of defined benefit, not defined contribution) or determining the retirement age (e.g. the uniformed services). Allocating specific amounts to the existing pension privileges means there is a need for collecting insurance premiums, taxes, or other duties that would allow the funding of these privileges. However, as important as financial costs are, other costs are associated with this problem. The most important non-economic effect of privileged pensions is the negative impact on the labour market.